Presença do SEDIN na história da luta pela educação infantil na cidade de São Paulo (2004-2012) - Oliveira, Maria Crisneilândia Bandeira de (2021)
This thesis has as object of study the Union of Educators of Childhood (SEDIN) and was concerned with locating the presence of this union institution in the history of early childhood education in the city of São Paulo. A reconstruction of the association's associative and unionist memory was carried out through interviews with its founders and militant teachers in São Paulo's early childhood education. The choice of these characters was due to their trajectories of struggles for public education, better working conditions and professional recognition as early childhood education workers and the transfer of daycare centers previously represented by the Secretariat of the Family Social Welfare (SEBES) to the Secretariat Municipal Education (SME). To this end, we cut out the history of early childhood education, contextualizing the social and popular movements that were precursors of struggles for education in the São Paulo city, identifying the Movement for the Struggle for Nurseries as an important driver of the social struggles that took place in the late 1970s. Movements how these paved the way and are in line with many of the struggles undertaken by SEDIN, which envisioned and founded their own union to represent early childhood education workers in the capital of São Paulo. The study period is the genesis of the union in 2004, until mid-2012. We seek support in the qualitative methodology. Six interviews were carried out, among which with the president and vice president of the union and with teachers and directors active in São Paulo's early childhood education, who reported their origins, trajectory in education and union participation in the struggles for professional, educational and social rights, about the motivations for the union's foundation, in the reflection of the collective organization and construction of the teacher's collective identity. From a theoretical-methodological point of view, we rely on authors who gravitate towards Marxism, we bring the contribution of scholars on the theme of teacher associations and unionism, especially those published by the Network of Researchers in Workers' Associations and Unionism in Education (ASTE Network). The investigative path revealed a history of early childhood education built on the clashes of social struggles for more education, dignity in the exercise of the profession and labor rights. The interviews showed the importance of the union as a space for political training and pedagogical actions, holding 16 congresses in education over its history. With regard to collective identity, these subjects joined forces in unions, created fronts of struggles through collective actions demonstrating that union participation enables the training and criticality of the teaching professional, which attributes them to the characteristics of struggles, being these a determinant and differential in the engagement of the actions carried out by the category, which characterized them as collective subjects building themselves throughout history as workers in education.